2021
DOI: 10.3390/molecules26071883
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Essential Oils from Roots and Aerial Parts of Carpesium cernuum and Their Antibacterial and Cytotoxic Activities

Abstract: Carpesium cernuum L., one of the two Carpesium species occurring in Europe, in the Far East and India, found use as a vegetable and a traditional medicinal remedy for several ailments. In the present study, compositions of essential oils distilled from roots and shoots of C. cernuum plants, cultivated in the open field, have been studied by GC-MS-FID supported by NMR spectroscopy. The analyses led to the identification of 120 compounds in total, of which 115 were found in aerial parts and 37 in roots of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Notably, 115 compounds were found in the aerial parts of Carpesium cernuum EOs, whereas only 37 compounds were found in the roots, which is consistent with previous studies. The proportions of the main compounds also vary greatly; for example, α-pinene (35%) and 2,5-dimethoxy-p-cymene (12%) were the predominant compounds in the EOs of shoots, whereas 2,5-dimethoxy-p-cymene (55%) and thymol isobutyrate (9%) were predominant in the EOs of roots [44].…”
Section: Multivariate Statistical Analysis Of Eo Chemical Profilesmentioning
confidence: 99%
“…Notably, 115 compounds were found in the aerial parts of Carpesium cernuum EOs, whereas only 37 compounds were found in the roots, which is consistent with previous studies. The proportions of the main compounds also vary greatly; for example, α-pinene (35%) and 2,5-dimethoxy-p-cymene (12%) were the predominant compounds in the EOs of shoots, whereas 2,5-dimethoxy-p-cymene (55%) and thymol isobutyrate (9%) were predominant in the EOs of roots [44].…”
Section: Multivariate Statistical Analysis Of Eo Chemical Profilesmentioning
confidence: 99%
“…Because EOs have multiple action targets, they can effectively avoid pathogen proliferation [ 10 ]. Several studies have shown that some EOs have significant antimicrobial activities against pathogens, such as Staphylococcus aureus , Listeria monocytogenes and Escherichia coli [ 11 , 12 , 13 ]. Therefore, EOs serve as a promising natural antibacterial ingredient in developing antibacterial agents for foods.…”
Section: Introductionmentioning
confidence: 99%